If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -26 = -7 + 9(b + 8) Reorder the terms: -26 = -7 + 9(8 + b) -26 = -7 + (8 * 9 + b * 9) -26 = -7 + (72 + 9b) Combine like terms: -7 + 72 = 65 -26 = 65 + 9b Solving -26 = 65 + 9b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-9b' to each side of the equation. -26 + -9b = 65 + 9b + -9b Combine like terms: 9b + -9b = 0 -26 + -9b = 65 + 0 -26 + -9b = 65 Add '26' to each side of the equation. -26 + 26 + -9b = 65 + 26 Combine like terms: -26 + 26 = 0 0 + -9b = 65 + 26 -9b = 65 + 26 Combine like terms: 65 + 26 = 91 -9b = 91 Divide each side by '-9'. b = -10.11111111 Simplifying b = -10.11111111
| -y^2+6y+x-9=0 | | 99=33x+9x+15 | | y-4=1/5(x-9) | | ln(x+3)=ln(6x-5) | | 35(6x-6)=1890 | | 4.9t^2-2t-50=0 | | 7×13/14--7 | | -4.9t^2+2t-50=0 | | -4z+9z=22 | | 30x+4x=102 | | (13x-4)+(9x+16)=180 | | 3(x)5(x)=30 | | -7x+6=7x-7 | | 4y+6=3y-8 | | 2w-13w=-33 | | 2x-5=x+6-5 | | 16/x^3=0 | | x+3=11+2x | | -2(6-7x)-2(1+3x)=3-3x-6 | | 3(x-2)=-15/2 | | x^7-3x^5-9x^3+27x=0 | | x^4(3m+2)x^2+m^2=0 | | Q+10+11q=30 | | 7x/8x=40 | | -9x=y+4 | | X+(x-5)+[2(x-5)]=85 | | 4x-6=39-5x | | -4(2k+8)=-8(4k+7) | | 2s(s-3)=4s+5 | | -4(-1+5n)=-4n+4 | | 12+5n=32forn | | (9x-13)+(17x+37)=180 |